Juridical Analysis of the Implementation of Consumer Protection Legislation in Digital Transactions - Nur Amalia Abbas; Lazarus Tri S; Nabitatus Sa’adah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Seeing the many conveniences presented by the internet, it is not surprising that Indonesia has recently continued to experience the development of online businesses ranging from small to large businesses. The development of technology in the business world has certainly encouraged the emergence of e-commerce using digital transactions. Digital transactions are transactions carried out by utilizing the internet. However, the widespread use of digital transactions is inseparable from the problems that occur such as fraud. This problem indicates that digital transactions carry significant risks. The method used is normative juridical research, where in this research data analysis is carried out based on literature relevant to consumer protection. The results obtained are that consumer protection is an important right and needs to be a concern of the government. Consumer protection needs to be tightened due to threats in the form of defective products, inaccurate information, and one-sided terms